Enhancing Children's Motor Skills through Clay Media at SD IT Al-Fajar - Olivine Alifaprilina Supriadi; Irfan Dwi Rahadianto; Tiara Radinska Deanda (Unram Journal of Community Service, 2026)
This community service project addresses the critical need for holistic education and physical-motor development at SD IT Al-Fajar Bandung. Modern educational trends often prioritize cognitive outcomes at the expense of physical and aesthetic dimensions, leading to a neglect of essential motoric skills in primary school children. Utilizing clay as a tactile and flexible medium, this program aimed to stimulate fine motor coordination among 50 elementary students. The intervention was designed within a holistic-integrative framework, combining creative art activities with Islamic core values such as Ihsan (excellence) and Amanah (trustworthiness). The workshop followed a structured pedagogical approach, beginning with university-led demonstrations of fundamental shapes and transitioning into autonomous creative exploration. Results indicated that the "duck shape" instructional model effectively bridged the gap between imitation and independent problem-solving, enhancing students' dexterity, spatial reasoning, and creative confidence. Furthermore, the provision of instructional modules ensures the sustainability of these practices within the school’s curriculum. This initiative demonstrates that integrating specialized tactile media into elementary education is a vital step toward nurturing the "whole child" and fulfilling institutional quality standards.